Clinical characterization, natural history, and neuroimaging of cerebellar ataxia after abdominal surgery - Procaci, Victor Rebelo; Silva, Thiago Yoshinaga Tonholo; Hora, Raphael Pinheiro Camurugy da; Barsottini, Orlando Graziani Povoas; Pedroso, José Luiz (Arquivos de Neuro-Psiquiatria, 2025)
The rates of complications after major abdominal surgeries remain high, despite the advances in pre- and postoperative care and surgical techniques. In these cases, neurological disorders mainly include stroke and delirium, with a high increase of morbidity. Ataxia is rarely a consequence of abdominal procedures like, more often being related to long-term complications of bariatric surgery due to chronic vitamin deficiency.To describe seven cases of ataxia following major abdominal surgeries and propose a prophylactic approach.A retrospective case series in which medical records of patients from the Ataxia Unit of Universidade Federal de São Paulo were evaluated from January 2007 to August 2024. We identified seven patients who developed acute cerebellar ataxia after gastrointestinal surgery. Demographic, clinical, laboratory, neuroimaging, and treatment data were extracted. Descriptive statistics was used to summarize findings.There were two cases that evolved with neurological improvement, and five remained with severe cerebellar ataxia. Brain imaging showed cerebellar atrophy in three patients and signs of Wernicke encephalopathy in two.This case series describes an unusual form of acute ataxia with poor outcomes, possibly related to complications from major abdominal surgery. Early intervention and prophylactic supplementation with vitamins B1 and B12 in patients receiving TPN should be considered to avoid such severe neurological complications.
Keywords: Postoperative Complications; Ataxia; Bariatric Surgery; Avitaminosis